Pemanfaatan Microsoft Excel Untuk Membantu Meningkatkan Kualitas Pembelajaran Mata Kuliah Matematika Kimia - I Nyoman Candra; Elvinawati; Hermansyah Amir (ALOTROP, 2023)
The purpose of this study was to improve learning activity and learning achievement of chemical education students in the odd semester who took the course Mathematics for Chemistry in the academic year of 2017/2018. This is a classroom action research consisting of three cycles, each of which includes planning, implementation, observation, and reflection. An observation sheet was used for collecting student and lecturer activities, whereas student achievement was collected using essay tests. The results show that the observation score for student activity for cycle 1, cycle 2, and cycle 3 were 20 (sufficient category), 25 (good category), and 27 (good category) respectively. Whereas, the average tests were 65.6; 80.4; and 81.3 for cycle 1, cycle 2, and cycle 3 respectively. It can be concluded that instruction of mathematics for chemistry courses aided by Microsoft Excel for students who took this course in the odd semester, the academic year of 2017/2018 could increase student learning activity and learning achievement. Keywords: Microsoft Excel; Mathematic for chemistry; classroom action research; learning achievement; learning activity.